Effects of Ethnically Diverse Photographic Stimuli on Preference and Discourse Tasks in African American and Caucasian American Adults. (February 2013) - Ramkissoon, Ishara; Dagenais, Paul A.; Evans, Kelli J.; Camp, Travis J.; Ferguson, Neina N.
This study determined whether using photographic stimuli displaying different ethnicity (African American vs. Caucasian American) influenced preference, word count, and number of content units produced by African American or Caucasian American participants. Six photograph pairs depicting common scenes were developed, differing only by model ethnicity. Participants sorted photographs by preference and described each photograph from which word count and content unit were determined. Each group showed significant preference for photographs of their own ethnicity. Caucasian Americans produced significantly more words than African Americans. Caucasian Americans also produced significantly more content units. Caucasian Americans produced more content units for African American scenes (nonsignificant). Results suggest that ethnic groups prefer photographic stimuli representing their own ethnicity. Other factors may influence the amount and content of speech produced. If African Americans typically produce less speech with less content than Caucasian American counterparts, separate normative data may be needed for each ethnic group.